Numerical Investigations on Material Flow During Indirect Extrusion of Copper-Clad Aluminum Rods - Kuhnke, Stefan; Sanabria, Vidal; Gensch, Felix; Nitschke, Renè; Mueller, Soeren (Frontiers in Materials, 2020)
In the extrusion of clad composites materials with different flow stresses are usually used. This causes an inhomogeneous material flow which can induce sleeve or core fracture. In the present study, the material flow during indirect extrusion of copper-clad aluminum rods was analyzed by means of experimental and numerical investigations throughout the process. In order to provide material models for the numerical analysis hot compression tests of the aluminum alloy EN AW-1080A and the copper alloy CW004A were carried out. The indirect extrusion was performed using a conical die with a semi die angle of 45 ° and an extrusion ratio of 14.8:1. The container was heated to 330 °C, while billet, die and ram were kept at room temperature. The extrusion trial was then modeled with the FEM based software DEFORM 2D. Cross sections were taken from the extruded rod and compared to the corresponding sections of the simulation with regard to the development of the equivalent copper cross section. As a result, the development of extrusion force and equivalent copper cross section could be clarified. The numerical investigations indicated a higher flow velocity for the aluminum core than for the copper sleeve at the bearing channel. Therefore, high tensile stresses and fractures of the copper sleeve were induced. Additionally, the validated numerical analysis made possible to determine the conditions for a successful co-extrusion of the analyzed copper-clad aluminum rod.